2021
DOI: 10.1111/ijcp.14868
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of palindromic rheumatism: A systematic review

Abstract: Palindromic rheumatism (PR) is an intermittent disease characterised by recurrent and self-resolving attacks of inflammation in the articular and peri-articular tissues. Attacks usually are monoarticular and last from a few hours to a few days. 1 During attacks, patients are asymptomatic. 1 Attacks mostly involve the knees, wrists, metacarpophalangeal joints and proximal interphalangeal (PIP) joints. 1 Finding autoantibodies associated with rheumatoid arthritis (RA) in a large percentage of patients with PR is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that PR progresses to RA in 10%‐66% of cases, mainly within 10 years of the onset of the disease 2‐4 . Although various studies show that treatment with disease‐modifying antirheumatic drugs (DMARDs) can control attacks of PR and prevent or postpone progression of disease to RA, no controlled studies have been performed about the efficacy of various DMARDs on the treatment of PR and there is no guideline for the treatment of PR 5 . Case series with limited number of cases and variable duration of follow up reported the efficacy of antimalarials, colchicine, gold and rituximab in the control of symptoms of PR 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that PR progresses to RA in 10%‐66% of cases, mainly within 10 years of the onset of the disease 2‐4 . Although various studies show that treatment with disease‐modifying antirheumatic drugs (DMARDs) can control attacks of PR and prevent or postpone progression of disease to RA, no controlled studies have been performed about the efficacy of various DMARDs on the treatment of PR and there is no guideline for the treatment of PR 5 . Case series with limited number of cases and variable duration of follow up reported the efficacy of antimalarials, colchicine, gold and rituximab in the control of symptoms of PR 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Case series with limited number of cases and variable duration of follow up reported the efficacy of antimalarials, colchicine, gold and rituximab in the control of symptoms of PR 5 . Based on the available evidence, it is recommended to start PR treatment with hydroxychloroquine (HCQ) 5 . However, HCQ could not control attacks of PR in 20%‐85% of cases 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, researchers have attempted to treat PR with anti‐RA drugs, such as NSAIDs, DMADs, glucocorticoids, and antimalarials, with some promising effects. Notably, the antimalarial drug hydroxychloroquine sulfate (HCQ) has gradually become a treatment option for long‐term management in patients with PR 13 . A prospective study showed that 47.78% of patients with PR treated with HCQ achieved complete disease control 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for PR are limited and there is no guideline for treatment. Antimalarial drugs, mainly hydroxychloroquine (HCQ), are the most commonly used medications 4 . However, antimalarials do not control attacks in all patients and others have used medications like methotrexate (MTX) 5,6 and rituximab 7 …”
Section: Introductionmentioning
confidence: 99%